Effective Ways of Teaching Listening of Arabic Language to Foreign Students - Iskanadar, Usmonov (International Journal of Formal Education, 2024)
This study aims to investigate whether students who learn Arabic language encounter specific difficulties in listening comprehension, explore the potential reasons for these challenges, and examine the impact of cultural background on the listening process. Understanding how cultural factors may influence listening abilities can provide valuable insights for language educators and curriculum developers. By examining the relationship between cultural background and listening comprehension, this study seeks to enhance our understanding of the complexities involved in foreign language learning. Addressing these issues can help educators tailor their teaching methods and materials to better support students from diverse cultural backgrounds, ultimately improving their language learning outcomes.